(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2026)
English pronunciation teaching in Nigeria tends towards external norms such as Received Pronunciation (RP), overlooking the systematic phonology of Nigerian English NE (Nigerian English) and reinforcing linguistic insecurity among learners. Research, including corpus-based work on the International Corpus of English–Nigeria (ICE–Nigeria), shows that NE has developed stable segmental and suprasegmental features shaped by multilingual contact and social factors. This paper integrates sociophonetic, World Englishes and English as a Lingua Franca perspectives to examine phonetic variation in NE and its implications for pedagogy. It highlights recurrent features - vowel neutralisation, diphthong monophthongisation, consonant substitution, cluster simplification and syllable-timed rhythm - as systematic patterns rather than random “errors”. On this basis, the paper proposes a four-step corpus-informed framework for pronunciation teaching: identifying common NE features, distinguishing those that affect intelligibility, using corpus evidence to set instructional priorities and reshaping teacher attitudes towards endonormative models. The study argues that aligning classroom practice with corpus evidence can promote intelligibility, affirm identity and support the codification of NE as a legitimate variety within global English.